Gluconacetobacter diazotrophicus AZ0019 requires functional nifD gene for optimal plant growth promotion in tomato plants - Pallucchini, Michele; Franchini, Martina; El-Ballat, Enas M.; Narraidoo, Nathalie; Pointer-Gleadhill, Benjamin; Palframan, Matthew J.; Hayes, Christopher J.; Dent, David; Cocking, Edward C.; Perazzolli, Michele; Fray, Rupert G.; Hill, Phil J. (Frontiers in Plant Science, 2024)
The nitrogen fixing diazotroph Gluconacetobacter diazotrophicus is a plant growth promoting bacterium able to colonise a wide range of host plants and is marketed commercially as a biofertiliser. The aims of this study were to investigate if biological nitrogen fixation (BNF) competency affects the growth promotion of inoculated tomato plants and to describe the colonisation mechanism of this bacterium in dicot systems.G. diazotrophicus wild type (Gd WT) or a nitrogen fixation impaired strain (Gd nifD -) were applied to hydroponically grown tomato plants in either the absence or presence of nitrogen.Phenotypic and colonisation data were collected 15 days post inoculation (dpi). qPCR analyses and tagged strains of G.diazotrophicus were employed to quantify and visualise the localisation of both Gd WT and Gd nifD -cells interacting with the plant.Inoculation with Gd WT strain led to increased plant height, fresh weight and chlorophyll content under both nitrogen limited and replete conditions. Inoculation with the Gd nifD -strain resulted in lower increases in fresh weight compared to the wild type bacterium, although significantly higher than the control, and no chlorophyll content increase. The two strains showed similar plant colonisation levels under both nitrogen conditions, suggesting that their effect cannot to be ascribed to a differential colonisation capability.These results indicate that a functional nifD gene is a fundamental requirement for optimal plant growth promotion (PGP) by G. diazotrophicus.